The circle of security parenting and parental conflict: a single case study - Pazzagli, Chiara; Laghezza, Loredana; Manaresi, Francesca; Mazzeschi, Claudia; Powell, Bert (Frontiers in Psychology, 2014)
The Circle of Security Parenting (COS-P) is an early attachment based intervention that can be used with groups, dyads, and individuals. Created in the USA and now used in many countries, COS-P is a visually based approach that demonstrates its central principles through videos of parent/child interactions. The core purpose of the COS-P is to provide an opportunity for caregivers to reflect on their child’s needs and on the challenges each parent faces in meeting those needs. Even though there is a wide range of clinical settings in which child/parent attachment is an important component of assessment there is limited empirical data on when and how attachment based interventions are appropriate for specific clinical profiles and contexts. The aim of this paper is to present a clinical application of COS-P in order to explore and reflect on some specific therapeutic tasks where it works and on some clinical indicators and contexts appropriate for its application. A single case study of a father, “M.” (43 yrs. old) in conflict for the custody of his 5yrs old daughter is reported. The Adult Attachment Projective Picture System (AAP), the Parenting Stress Index, the Strengths and Difficulties Questionnaire, and the Parental Alliance Measure, were administered pre- and post-intervention. The clinical signiﬁcance analysis method revealed that numerous changes occurred in the father. The AAP showed improvements in the level of agency of self. M. made gains in his capacity to use internal resources and to increase his agency of self. M. was classified as recovered in his perception of the child’s functioning and as improved in his parenting stress and parenting alliance with the mother. Considerations on specific contexts and clinical indicators for the application of COS-P are proposed.